Persepsi Nasabah terhadap Akad Rahn pada Pegadaian Syariah - Sri Widiastuti; Nurse Fatimah MZ (AL-Muqayyad, 2021)
This research was motivated by the author's preliminary observations regarding customers' points of view between Sharia Pawnshops, and conventional Pawnshops were the same, some customers thought that Sharia Pawnshops also apply interest, even though the system were different. The purposes of this study were to find out how the Rahn contract, and the customer's perception of the Rahn at the Syariah Pawnshops. Data analysis used qualitative descriptive by deductive, and inductive methods. The results showed that most of the customers did not understand the Rahn, but they believed that the pawn products available at the Sharia Pawnshop and the pawn products in conventional pawnshops were the same. Furthermore, the implementation of the Rahn contract at the Sharia Pawnshop was under Islamic roles because there were no rules that violate Islamic law.